2017
DOI: 10.1111/scd.12256
|View full text |Cite
|
Sign up to set email alerts
|

Healing of self‐inflicted thermal injury of palatal mucosa by low‐level laser therapy

Abstract: Self-inflicted injury to oral mucosa is a rare entity. These injuries can be premeditated, accidental, or can result from an abnormal habit. These uncommon gingival injuries can sometimes test the clinician's diagnostic abilities as well as treatment planning skills. In conventional treatment, removal of etiology and application of topical drugs is usually sufficient for healing. However, some cases require alternative or adjunctive wound healing methods. Low-level laser therapy (LLLT) has been reported to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…When compared with antibiotic therapy used alone, 10 the present clinical results demonstrated a substantial relief from the painful sensation in a short period of time, achieving healthy tissue marked by the absence of bleeding in few days and more organized wound healing, which resulted from the combination with/activation by light and protocols proposed here. 26,27,34,35 In the present report, no pain scale measurement was applied (e.g. visual analogic scale).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared with antibiotic therapy used alone, 10 the present clinical results demonstrated a substantial relief from the painful sensation in a short period of time, achieving healthy tissue marked by the absence of bleeding in few days and more organized wound healing, which resulted from the combination with/activation by light and protocols proposed here. 26,27,34,35 In the present report, no pain scale measurement was applied (e.g. visual analogic scale).…”
Section: Discussionmentioning
confidence: 99%
“…Relative to protocols, the number of wound healing sessions varied among studies. Ahad et al 34 used 5 sessions (10 days) to reach a substantial effect on a self-inflicted thermal injury in the palate by using a 1 W output laser, whereas da Silva Neves et al 35 used a higher dosage (60 J/ cm 2 ) with 0.3 W applied in 7 sessions to promote faster wound healing after the removal of a connective tissue graft in the palatal region. Comparing these protocols with those used in the present case was difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines play a major role in the pathogenesis of anti-cancer therapy induced OM and understanding their role may be helpful in developing management strategies. 10,22,23 Among these, are the pro-inflammatory cytokines IL-6 and TNF-α which were studied and conducted in more than one study, [22][23][24] in which they examined the impact of LLLT on inflammatory cytokines during COM among patients undergoing hematopoietic stem cell transplantation. They found a significant difference in plasma level of IL-10 only.…”
Section: Discussionmentioning
confidence: 99%
“…In skin wound healing, it is known that this process is complicated and depends on many different cell types and their interactions in sophisticated temporal sequences . Previous studies have revealed that low‐level laser therapy (LLLT) effectively improved wound healing through the promotion of the cell cycle, whereas heat injuries upregulated the expression of heat shock proteins and increased cell viability . Shallow heat injury was also reported to manipulate the XIST/miR‐29a/LIN28A pathway to restore normal tissue morphology and functions …”
Section: Introductionmentioning
confidence: 99%